Sex differentiation of morphological and motor features in children and youth - Burdukiewicz, A. (Human Movement, 2004)
Purpose. Sexual dimorphism refers to diversity between females and males, which occurs in morphology, physiology and behavior. The aim of the paper was to examine sex differentiation in the development of morphological and functional features in children and youths from rural areas 7-14 years, using the results of semilongitudinal examinations from 7 to 10 and 11 to 14 years (boys n = 155 and 224, girls n = 151 and 195).